Interreligious perspectives on Surrogate Motherhood - Ladas, Ioannis (Bioethica, 2024)
Surrogate motherhood raises a variety of ethical, legal, theological, and sociological questions. Discussions on this topic often become heated, particularly when considering the use of a woman’s body to carry a pregnancy on behalf of another individual—married or unmarried, male or female—with an ovum that, in most cases, has no biological connection to her and is legally recognized as belonging to the commissioning party or parties post-birth. On one side, issues of self-determination, solidarity, and compassion are debated, while on the other, dignity, the sanctity of life, commodification, and exploitation are concerns. This article, without overlooking these significant issues, attempts an interreligious examination of surrogate motherhood to elucidate how the three major monotheistic religions, along with Hinduism and Buddhism, assess, interpret, and understand this practice. The aim is to highlight both converging and diverging positions across different views and to more fully comprehend the various theological and cultural dimensions that shape the contemporary bioethical understanding of this issue.